Pengaruh Financial Literacy, Risk Tolerance, dan Religiusitas terhadap Keputusan Investasi di Pasar Modal Syariah (Studi pada Mahasiswa FEBI UIN K.H. Abdurrahman Wahid Pekalongan) - M. Khotim; Dwi Novaria Misidawati (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2024)
The phenomenon of investment in the capital market is increasingly developing, especially the sharia capital market. Establishing a sharia capital market is the right decision considering that Indonesia is the country with the largest number of Muslims. The sharia capital market should be helped by the presence of a large Muslim community. However, in reality the level of public interest in the Islamic capital market has decreased. Irwan Abdullah as Head of the IDX Sharia Capital Market Division said that the market share of the sharia capital market decreased after the Covid-19 pandemic. Determining investment decisions is related to several things, such as financial literacy, risk tolerance, and religiosity. The aim of this research is to analyze the influence of financial literacy, risk tolerance and religiosity on the decision to invest in the sharia capital market among FEBI UIN K.H Abdurrahman Wahid Pekalongan students. This type of research is field research or field research with a quantitative approach. The population in this study was 2569 FEBI students. The data collection method is a questionnaire that has been tested as valid and reliable using a sample of 100 respondents. This research uses a multiple linear regression test data analysis method with the help of SPSS 21. The results of this research show that financial literacy and religiosity influence investment decisions. Meanwhile, risk tolerance does not influence investment decisions. Then simultaneously financial literacy, risk tolerance and religiosity influence investment decisions.